Program Edukasi Energi Terbarukan Sebagai Alternatif Teknologi Ramah Lingkungan di MTS Negeri 1 Mataram - Sultan, Sultan; Muljono, Agung Budi; Nrartha, I Made Ari; Ginarsa, I Made; Sasongko, Sudi Maryanto Al; Hadi A, Muh. Saihul; Yadnya, Made Sutha (Universitas Mataram, 2024)
Global warming and the environmental impacts of fossil fuels are very important to understand, especially for the younger generation, including students. Geographically, MTs Negeri 1 Mataram is located in the Mataram city area with a distance of approximately 1 kilometer from the Mataram University campus, which is the place of duty for the team carrying out this service. The method for implementing this service is through socialization and education about the basic concepts of solar power plants, how they work, and their environmental and social benefits through various stages including presentations, discussions, practical demonstrations of PLTS modules, and assessing student understanding through post-tests. and pre-test. Practice demonstration of PLTS modules. Evaluation of the 20 students who took part in this activity showed an increase in their awareness regarding the importance of PLTS in sustainable energy and environmental conservation, because the average post-test and pre-test score was above 83. This is expected to encourage active participation of students in supporting renewable energy in the future